Universal coverage and utilization of free long-lasting insecticidal nets for malaria prevention in Ghana: a cross-sectional study - Afagbedzi, Seth Kwaku; Alhassan, Yakubu; Kenu, Ernest; Malm, Keziah; Bandoh, Delia Akosua Benewaah; Peprah, Nana Yaw; Ansah, Otubea Owusu; Guure, Chris (Frontiers in Public Health, 2023)
Background: Malaria is one of the leading causes of mortality and morbidity, especially among children and pregnant women. The use of Long-Lasting Insecticide Nets (LLINs) has been recognized and prioritized as a major intervention for malaria prevention in Ghana. This study aims to establish the factors influencing the universal coverage and utilization of LLINs in Ghana. Methods: The data used for this study was from a cross-sectional survey carried out to assess LLINs ownership and use in 9 out of the 10 old regions of Ghana from October 2018 to February 2019 where free LLIN distribution interventions were implemented. The EPI “30 x 7” cluster sampling method (three-stage sampling design) was modified to “15 x 14” and used for the study. A total of 9,977 households were interviewed from 42 districts. Descriptive statistics using percentages as well as tests of associations such as Pearson chi-square and the magnitude of the associations using simple and multivariable logistic regression were implemented. Results: Of the 9,977 households in the study, 88.0% of them owned at least one LLIN. In the rural and urban areas, 90.8% and 83.2% of households, respectively, owned at least one LLIN. The point mass distribution (PMD) approach resulted in a 44% increase in universal coverage of LLINs in rural areas compared to urban areas (AOR: 1.44, 95% CI: 1.02-2.02). There were 29 higher odds of households being universally covered if they received LLIN from the PMD (AOR: 29.43, 95% CI: 24.21-35.79). Households with under-five children were 40% more likely to utilize LLIN (AOR: 1.40, 95% CI: 1.26-1.56). Respondents with universal coverage of LLIN had 25% increased odds of using nets (AOR: 1.25 95% CI: 1.06-1.48). Rural dwelling influences LLIN utilization, thus there was about 4-fold increase in household utilization of LLINs in rural areas compared to urban areas (AOR: 3.78, 95% CI: 2.73-5.24). Conclusions: The difference in universal coverage between households who received LLINs from the PMD campaign and those who did not may be explained by the effectiveness of the PMD programme to achieve sustained universal coverage of LLINs for malaria prevention.